Characteristics of Liquid Products in Supercritical Water Gasification of Municipal Sewage Sludge by Continuous Flow Tubular Reactor - Adar, Elanur; Ince, Mahir; Bilgili, Mehmet Sinan (SPRINGER, 2020)
Sewage sludge is a by-product of wastewater treatment, containing high water and organic content. Supercritical water gasification provides sustainable treatment for biomass sources such as sewage sludge. In this study, the effects of operating conditions (temperature, solid matter content and catalyst) and raw material properties on the resulting liquid products were determined in order to exhibit the success of this innovative technology for treatment and disposal of municipal sewage sludge using a continuous flow pilot-scale tubular reactor for the first time in Turkey. As a result of the study, it was determined that the higher the temperature, the higher the quality of the liquid product. TOC removal efficiencies increased from 84.4% to 99% with increasing the temperature from 450 to 650 degrees C, for 1% solid matter content. The pollutant concentrations in the liquid products increased by increasing the solid matter content of the raw sludge from 1 to 2%. This situation has been eliminated by the catalyst (KOH) addition, resulting in a very transparent liquid product. Additionally, TOC removal of 99.8% was obtained after addition of 2% catalyst. Thus, supercritical water gasification (SCWG) has been considered as a notable technology for the treatment and disposal of sewage sludge without the need of additional pre- or post-treatment. [GRAPHICS]
Keywords: Supercritical water gasification; Municipal sewage sludge; Liquid product quality; Pilot scale reactor; KOH; Catalyst; HYDROTHERMAL GASIFICATION; CATALYTIC GASIFICATION; HEAVY-METALS; WASTE-WATER; BIOMASS; LIQUEFACTION; PROTEINS; MODEL; MANAGEMENT; RESIDUES; Environmental Sciences & Ecology